Clinical and Pathophysiological Effects of Inhalation Exposure to Magnesium Carbonate and Rubber-Derived Pollutants in Indoor Climbing Facilities: A Review - Karczewski, Jakub Dariusz; Białek, Aleksandra; Sadok, Aleksandra; Kubas, Wojciech; Niemcewicz, Wojciech Jan; Ryń, Kamila; Koźlicka, Aleksandra; Klajda, Jakub; Czerniakowski, Mikołaj; Gorczyca, Zuzanna (Quality in Sport, 2026)
Background. Indoor climbing has experienced exponential growth in global popularity. Consequently, athletes and facility staff are spending increasing amounts of time in enclosed environments characterized by unique air quality challenges. The extensive use of climbing chalk (predominantly magnesium carbonate) to enhance friction, combined with the continuous abrasion of specialized rubber from climbing shoes, generates high concentrations of airborne particulate matter (PM). The clinical and pathophysiological implications of prolonged inhalation of these specific pollutants remain a critical area of occupational and sports medicine. Aim. To systematically review the current evidence regarding the indoor air quality of climbing facilities, focusing on the clinical and pathophysiological effects of inhalation exposure to magnesium carbonate and rubber-derived particulate matter on the human respiratory system.